Perception of Ease, Risk, and Benefits in Online Loans: A Study in Lower Middle Communities - Nasith, Ali (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Technological advancements have provided easier and faster access to financial services, including through online lending applications, which can have significant implications for individual finances and household economic stability. As such, there is an urgent need to explore how their perceptions of the ease, risks and benefits of using online lending applications may influence their financial behavior. The purpose of this study is to gain a deeper understanding of the factors that influence the perceptions of the lower middle class towards online loan applications and also to provide a solid foundation for public policy designers and financial service providers. This research makes use of descriptive quantitative methods. In this study, a questionnaire-based interview serves as the research tool. One hundred participants were selected at random from the pool of potential respondents. Multiple linear regression is the data analysis tool employed in this research. According to the findings, individuals' perceptions of the ease and advantages of using online lending services (pinjol) significantly impact their behavior, whereas the impact of perceived risk is not statistically significant.